Odpowiedzi

2010-03-04T19:43:47+01:00
-4(x+y)=-4x-4y
-3a(jedna trzecia -a)=-a+3a=2a
jedna druga(2a-4b+1)=a-2b+1/2
3p(2r+5p-1)=6pr+15p^-3p


(-4x+8):4=-4x/4+2
5x+10y dzielone kreską ułamkową na 5=5x/5+10y/5
2010-03-04T19:44:10+01:00
4(x+y)=4x+4y
-3a(jedna trzecia -a)=-4a+3akwadrat
jedna druga(2a-4b+1)=a-2b+jedna druga
3p(2r+5p-1)=6pr+15p kwadrat-3p

Przekształć ilorazy na sumy

(-4x+8):4=-x+2
5x+10y dzielone kreską ułamkową na 5=x+2y
2010-03-04T19:45:01+01:00
Przekształć iloczyny na sumy
-4(x+y)=
= -4x -4y

-3a(jedna trzecia -a)
-3a*1/3 - 3a*(-a) =
= a + 3a²

jedna druga(2a-4b+1)
= 1/2*2a -1/2*4b + 1/2*1=
= a -2b + 1/2

3p(2r+5p-1)=
= 3p*2r + 3p*5p - 3p*1=
= 6pr + 15p² -3p

Przekształć ilorazy na sumy

(-4x+8):4 =
= (-4x ):4 + 8 : 4 =
= -x + 2

5x+10y dzielone kreską ułamkową na 5
= (5x + 10y ): 5 =
= 5x : 5 + 10y : 5=
= x + 2y